Electoral disinformation looking through the lens of Tsek.ph fact checks - Chua, Yvonne T.; Soriano, Jake (2020)
Access online through this link: https://www.plarideljournal.org/article/electoral-disinformation-looking-through-the-lens-of-tsek-ph-fact-checks
Keywords: Disinformation; Fact checking; Elections